Rheological, mechanical, and microstructural properties of engineered geopolymer composite (EGC) made with ground granulated blast furnace slag (GGBFS) and fly ash - Xinhua Cai; Jinjing Yin; Xian Xu; Duo Zhang; Yamin Wang (Journal of Materials Research and Technology)
Ground granulated blast-furnace slag (GGBFS) and fly ash (FA) were used as precursors to prepare Engineered Geopolymer Composite (EGC) based on the binary binder system, and the effects of GGBFS content and curing time on the mechanical properties as well as the microstructure were investigated. Results showed that the increase of GGBFS content enhanced the yield stress and plastic viscosity of the fresh EGC mixtures, manifesting a more noticeable shear thickening behavior. As the GGBFS content increased, the compressive strength of EGC was found to rise monotonically, while the tensile characteristics changed slightly, exhibiting distinct strain hardening behavior that contributes to the crack control capacity and tensile ductility. It needs to be pointed out that, all EGC groups in this work exhibited high tensile ductility (ultimate tensile strain >4%), high tensile strength (between 4.4 and 6.8 MPa), and good crack control capacity (an average crack width below 90 μm). Furthermore, SEM-EDS results indicated that the incorporation of GGBFS caused a shift from N-A-S-H to C-A-S-H gels, with an increase in Ca/Si, while Al/Si remained at the same level. The findings of this paper are anticipated to promote EGC's practical applications by guiding the material optimization for enhanced technical performance and sustainability.